Investigation on The Effect of Compation And Compressive Strength Of Clayey Soil Using Glass Fiber - Ibrahim, Abu Bakar (2018)
Construction or roads and other civil engineering structures on a loose or soft soil is risky due to its high compressibility, low shear strength and high permeability. In such situations it is general practice to modify the soil properties by blending with different materials such as lime, cement and fly ash or by reinforcing the soil. The soil that was used for this research was classified as clay soil and the stabilizer used in Glass fiber.